Sporopollenin, The Least Known Yet Toughest Natural Biopolymer - Mackenzie, Grahame; Boa, Andrew N.; Diego-Taboada, Alberto; Atkin, Stephen L.; Sathyapalan, Thozhukat (Frontiers in Materials, 2015)
Sporopollenin is highly cross-linked polymer composed of carbon, hydrogen, and oxygen that is extraordinarily stable and has been found chemically intact in sedimentary rocks some 500 million years old. It makes up the outer shell (exine) of plant spores and pollen and when extracted it is in the form of an empty exine or microcapsule. The exines resemble the spores and pollen from which they are extracted, in size and morphology. Also, from any one plant such characteristics are incredible uniform. The exines can be used as microcapsules or simply as micron-sized particles due to the variety of functional groups on their surfaces. The loading of a material into the chamber of the exine microcapsule is via multi-directional nano-diameter sized channels. The exines can be filled with a variety of polar and non-polar materials. Enzymes can be encapsulated within the shells and still remain active. In vivo studies in humans have shown that an encapsulated active substance can have a substantially increased bioavailability than if it is taken alone. The sporopollenin exine surface possesses phenolic, alkane, alkene, ketone, lactone, and carboxylic acid groups. Therefore, it can be derivatized in a number of ways, which has given rise to applications in areas, such as solid supported for peptide synthesis, catalysis, and ion-exchange chromatography. Also, the presence of the phenolic groups on sporopollenin endows it with antioxidant activity.